Development Strategy of Maroon Mangrove Edupark in Semarang City, Central Java: STRATEGI PENGEMBANGAN MAROON MANGROVE EDUPARK DI KOTA SEMARANG, JAWA TENGAH - Janne Hillary; Titik Ekowati; Bambang Mulyanto Setiawan (Media Konservasi, 2019)
Maroon Mangrove Edupark (MMEP) is one of the most visited mangrove forests in Semarang. It is located close to Maroon beach and Ahmad Yani International Airport. MMEP was classified as a new tourism site that expected to provide an economic value for local community. Economic benefits that was obtained by visitors and manager can be known through economic valuation. Development strategy is needed to maintain its existence and bring a great economic benefit in the future. The primary aim of this study was to analyze MMEP’s sustainable preserve strategies. Economic valuation as well as internal and external factors evaluation can be used as a reference in managing and developing MMEP. Components of economic valuation were total economic value and price of tourist entrance ticket. Individual Travel Cost Method (ITCM) was used to analyze the economic value of MMEP. Total economic value of MMEP was IDR 421.169.436. The tourism potential that has been utilized was only 36.83% of the total economic value. The value can be increased by increasing MMEP's received costs directly from the travel cost incurred by respondents. Willingness To Pay (WTP) value that can be used as a reference in determining a tourist entrance fee at MMEP was IDR 9.000. The condition of MMEP management was in quadrant III. The step should be taken to develop MMEP is the Weakness-Opportunity (WO) conservative strategy, which is strategy to minimize the weaknesses and to maximize the opportunities. Keywords: economic valuation, individual travel cost method, SWOT analysis, conservatif strategy, mangrove